PERAN GURU KELAS DALAM MEMANDIRIKAN PESERTA DIDIK (Studi di SDN 31 Kinali Pasaman Barat) - Putra, Fadil Eka; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
ABSTRACTThis research is motivated by the role of the teacher in the classroom be autonomous learners who have not been as expected, the focus of this study include: 1) The role of the teacher in the classroom be autonomous learners related to learning activities. 2) The role of the teacher in the classroom learners be autonomous related discipline. This research is qualitative. Intake of research subjects is done by using snowball sampling technique. Key informants in this study were classroom teachers, amounting to 6 people. Additional informants were principals and learners that consists of 4 people. Data were collected through interviews, observation and documentation of the role of the teacher in the classroom be autonomous learners. The research findings revealed that the students are given the punishment if the students do not follow the lessons well, for the teacher directs students to be more active in learning to be more motivated to learn. When students arrive late to school teachers provide guidance / advice and there is also a form of punishment, this is done so that learners do not repeat the mistakes that happened on this day is done again the next day, and studienst understand the regulations that apply in the school